Comparative effectiveness of rituximab, abatacept, and tocilizumab in adults with rheumatoid arthritis and inadequate response to TNF inhibitors: prospective cohort study. (24th January 2019) - Gottenberg, Jacques-Eric; Morel, Jacques; Perrodeau, Elodie; Bardin, Thomas; Combe, Bernard; Dougados, Maxime; Flipo, Rene-Marc; Saraux, Alain; Schaeverbeke, Thierry; Sibilia, Jean; Soubrier, Martin; Vittecoq, Olivier; et al.
Abstract: Objective: To compare the effectiveness and safety of three non-tumour necrosis factor (TNF) α inhibitors (rituximab, abatacept, and tocilizumab) in the treatment of rheumatoid arthritis. Design: Population based prospective study. Setting: 53 university and 54 non-university clinical centres in France. Participants: 3162 adults (>18 years) with rheumatoid arthritis according to 1987 American College of Rheumatology criteria, enrolled in one of the three French Society of Rheumatology registries; who had no severe cardiovascular disease, active or severe infections, or severe immunodeficiency, with follow-up of at least 24 months. Intervention: Initiation of intravenous rituximab, abatacept, or tocilizumab for rheumatoid arthritis. Main outcome measure: The primary outcome was drug retention without failure at 24 months. Failure was defined as all cause death; discontinuation of rituximab, abatacept, or tocilizumab; initiation of a new biologic or a combination of conventional disease modifying antirheumatic drugs; or increase in corticosteroid dose >10 mg/d compared with baseline at two successive visits. Because of non-proportional hazards, treatment effects are presented as life expectancy difference without failure (LEDwf ), which measures the difference between average duration of survival without failure. Results: Average durations of survival without failure were 19.8 months for rituximab, 15.6 months for abatacept, and 19.1 months for tocilizumab. Average durations were greater with rituximab (LEDwf 4.1, 95% confidence interval 3.1 to 5.2) and tocilizumab (3.5, 2.1 to 5.0) than with abatacept, and uncertainty about tocilizumab compared with rituximab was substantial (−0.7, −1.9 to 0.5). No evidence was found of difference between treatments for mean duration of survival without death, presence of cancer or serious infections, or major adverse cardiovascular events. Conclusion: Among adults with refractory rheumatoid arthritis followed-up in routine practice, rituximab and tocilizumab were associated with greater improvements in outcomes at two years compared with abatacept.